Work Environment as the Primary Driver of Employee Performance: Evidence from an Automotive Service Firm in Southeast Sulawesi - Nugraha, Alim Adhitya; Razak, Abdul; Hakim, Abdul (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Employee performance in automotive service firms depends not only on formal organizational arrangements but also on the quality of the work environment experienced by employees. This study examines the effects of organizational style and work environment on employee performance at PT Kendari Berlian Motor, Southeast Sulawesi. A quantitative associative design was applied using a census of 45 employees. Data were collected through a structured Likert-scale questionnaire and analysed using descriptive statistics, classical assumption tests, and multiple linear regression. The results show that organizational style and work environment jointly have a significant effect on employee performance (F = 381.041, p < .001), explaining 94.8% of performance variance. However, organizational style does not have a significant partial effect (B = 0.038, t = 1.244, p = .220), while work environment has a strong positive and significant effect (B = 0.762, t = 26.516, p < .001). These findings indicate that a supportive, safe, comfortable, and socially enabling work environment is a more immediate driver of employee performance than formal organizational style in a relatively young automotive service organization.